Pollen and Macrofossil Study of an Interglacial Deposit in Nova Scotia - Mott, R.; Anderson, T.; Matthews, J. (Géographie physique et Quaternaire, 1982)
ABSTRACT Overburden removal for quarrying operations at the Milford Gypsum Quarry, East Milford, Nova Scotia, exposed 2 m of compacted and distorted peat and organic clays with abundant plant remains, associated with inorganic and laminated clays and sands. The non-glacial sediments were underlain by a grey till-like deposit and overlain by more than 20 m of red till. Wood (Larix sp.) from the nonglacial sediments produced a radiocarbon date of > 50,000 years BP (GSC-1642). Pollen analysis of the organic sediments shows a basal assemblage characterized by a variety of hardwood pollen genera including Fagus, Ulmus, Acer, Quercus and Tilia. Higher in the sequence Betula pollen increases and becomes the dominant pollen type. Towards the upper part of the organic unit, Picea and Abies balsamea replace the hardwood genera. Alnus is the most abundant pollen type at the top of the sequence. Wood, seeds, moss and Coleoptera remains add to the environmental reconstruction. The evidence as a whole leads to the conclusion that the latter part of an interglacial interval, probably the Sangamon, is represented. Hardwood forests dominated by a variety of thermophilous hardwood genera attest to a climate at least as warm as the present in the area. As the climate deteriorated, Betula became dominant. Continued cooling induced a transition to coniferous forests in which Picea and Abies balsamea predominated.